ANALISIS PENDAPATAN PETERNAK KAMBING PE DI KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Andrean, Ade; Media Agus Kurniawan (Journal of Innovation Research and Knowledge, 2024)
This research aims to determine the income of Etawa crossbreed goat breeders regarding the feasibility of investing in a farm in Beringin District, Deli Serdang Regency, with a focus on whether the investment carried out is worthy of being continued or not. This analysis is carried out using the Payback Period (PBP), B/C Ratio, Net Present Value (NPV) and Internal Rate of Return (IRR) methods. The research method used in this research uses primary and secondary data. The research was carried out on five farms with results, Mr. Krisna's breeder Payback Period (PBP) 2.15, B/C Ratio 1.28, Net Present Value (NPV) 156,575,825 and Internal Rate of Return (IRR) of 38%, Mr. Anto's breeder Payback Period (PBP) 2.85, B/C Ratio 1.13, Net Present Value (NPV) 275,012,420 and Internal Rate of Return (IRR) of 29%, breeder Mrs. Yani Payback Period (PBP) 3.33, B/C Ratio 1.00, Net Present Value (NPV) 51,300,723 and Internal Rate of Return (IRR) of 18%, breeder Mr. Sumirat Payback Period ( PBP) 1.56, B/C Ratio 1.47, Net Present Value (NPV) 281,090,710 and Internal Rate of Return (IRR) of 71%, breeder Mr. Sunoto Payback Period (PBP) 1.71, B/C Ratio 1.42, Net Present Value (NPV) 215,728,737 and Internal Rate of Return (IRR) 57%. With an interest rate value of 13% for each farm, it is concluded that the five businesses can be declared viable based on an IRR value greater than 13% and declared viable based on the other three analyses